Assessment of Knowledge, Attitude and Practices of the General Public in Combating COVID-19 (Medical Forum Monthly, 2021)
Objective: To know knowledge, attitude and practices of the general public in combating Covid-19.Study Design: Prospective study.Place and Duration of Study: This study was conducted at the at two tertiary care hospitals of Khyber Pakhtunkhwa i.e. Lady Reading hospital Peshawar, and Mardan Medical Complex Mardan from 1st January 2021 to 30 June 2021.Materials and Methods: A pre-validated online questionnaire was distributed among the general population. Adequate knowledge was assigned as a score of > 4 (range: 0–8) and good perception as a score of > 3 (range: 0–5). Chi-square test was used to determine the significance of difference in knowledge and perception of COVID-19 with socio-demographic characteristics. Logistic regression analysis was run to identify factors associated with adequate knowledge and perception. P < 0.05 was considered as significant.Results: A large no of participants had appropriate knowledge of Covid 19 disease (98.9%). Regarding attitudes of people COVID-19 is a treatable disease, agreed 28.5% disagreed. 9.1%. Neutral 25.8%, strongly agreed 31.5% and strongly disagreed 3.4%. COVID-19 can be avoided by washing hands and wearing facemasks Agreed 26.8%, disagreed 1.7%. Neutral 4.9%, strongly agreed 64.5% and strongly disagreed 0.4. Regarding practices, I avoid unnecessary going out of my home Missing 2.3%, always 64.3%. never 1.1%. Often 22.0%rarely .23% and sometimes 8.0%.Conclusion: Albeit the surge of COVID-19 cases in Pakistan, the participants demonstrated an overall adequate knowledge and good perception towards COVID-19.